The effect of micro-plastics on the growth and development of Eisenia fetida (Savingy, 1826) in vermiculture - Andrey S. Babenko; Alexander V. Kurovskij (Acta Biologica Sibirica)
The effect of different concentrations of e-waste plastic (acrylonitrilebutadiene styrene) in vermiculture on the growth and development of the compost earthworm E. fetida was studied. It was shown that at low concentrations of microplastics (1%) in vermiculture, earthworms practically do not reduce their growth and development indicators, while with an increase in the plastic concentration to 5–10%, the number of cocoons and juveniles decreases, and the growth of earthworm biomass slows down. Avoidance of the substrate and death of worms are not observed even with a relatively high (10%) proportion of plastic in the composted mixture.